Commercial and social activities of Indonesian Islamic banks: do they relate? - Budi Sukardi; Muhammad Alan Nur; Fachrurazi Fachrurazi; Fuad Dhiya Ul Husaen; Eko Asmanto (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — This study investigates the relationship between commercial and social activities in Indonesian Islamic banks.Method — This study employed a Panel Vector Error Correction Model (PVAR) model with Impulse Response Function (I.R.F), Variance Decomposition (V.D.C), and Granger Causality. Observations were conducted from 2010 to 2020 on eight Islamic banks in Indonesia, representing 72.72 percent of the total Islamic banking population in Indonesia. The collecting of data pertains to the yearly financial report. Social activities are based on the amount of zakat fund distribution (ZKT) and benevolence fund distribution (DKB). Commercial activities are based on Islamic banking financial ratios that are proxied by Return on Assets (ROA), Financing to Deposit Ratio (FDR), and Non-Performing Financing (NPF).Result — The results showed that social activities in Indonesian Islamic banks are influenced by their commercial activities, but it does not apply vice versa. In other words, there is a one-way relationship between commercial and social activities in Indonesian Islamic banks.Contribution — This study contributes by studying the relationship between commercial and social activities by using the PVAR model with the analysis of Impulse Response Function (I.R.F), Variance Decomposition (V.D.C), and Granger Causality which so far have not been explored.